Student learning outcomes with the application of the team game tournament learning model in review of student motivation in class XI - D Une, Putri Mutia; Yahya, Lailany; Isa, Dewi Rahmawaty (Program Studi Pendidikan Matematika, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to know whether or not there is an influence between the learning outcomes of students who are taught using the TGT cooperative learning model and that of using direct learning in terms of student motivation. This is a quasi experimental study using Treatment By Level design which is carried out in class XI SMA in Wonosari in the even semester of the 2022/2023 academic year. The study samples are the students in class XI, totalling 71 students. The data are obtained from instruments in the form of multiple choice and questionnaires. Each is used to test mathematics learning outcomes and student motivation. Data analysis uses a two-way analysis of variance and a Scheffe test. The findings show that: 1) The learning outcomes of students who are taught using the TGT learning model are higher than that of using the direct learning model. This content evidenced results obtained Fcount = 12.701 and Ftable = 3.98, so Fcount > Ftable causes the (H1) to be accepted. 2) There is interaction influence between the learning model and students' motivation on students' mathematics learning outcomes. This content evidenced results obtained Fcount = 5.1913 and Ftable = 3.98, so Fcount > Ftable causes the (H1 ) to be accepted. 3) The learning outcomes of students with high motivation who are taught using the TGT learning model are higher than that of using direct learning model. This content evidenced results obtained Fcount = 16.472 and Ftable = 3.74, so Fcount > Ftable causes the (H1 ) to be accepted. 4) The learning outcomes of students with low motivation who are taught using the TGT learning model are lower than that of using direct learning model. This content evidenced results obtained Fcount = 1.420 and Ftable = 3.74, so Fcount < Ftable causes the (H0 ) to be accepted.